More scenes from Shakespeare twenty cuttings for acting and directing practice - Shakespeare, William 1564-1616 (Meriwether Pub., 1999)
A collection of twenty short scenes from six Shakespeare plays: "Macbeth," "Much Ado About Nothing, " "A Midsummer Night's Dream, " "King Lear, " "As You Like It, " and "The Taming of the Shrew." Each scene is preceded by a plot synopsis and descriptions of the characters.